Independence and Accountability of Monetary and Fiscal Policy Committees - Alexander Mihailov; Katrin Ullrich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
The democratic accountability of policymaking institutions which are autonomous within delegated mandates has not received as much attention as their independence. We analyze in a theoretical model the effects of accountability in the form of possible overriding of economic policy decisions by the government under different degrees of independence of expert committees conducting monetary and fiscal policy. The equilibrium outcomes of such alternative institution-design frameworks are compared according to key macroeconomic performance criteria. Our results stress the trade-off between anchoring inflation expectations on target and output stabilization that is not solved with accountability.
Keywords: E63; E61; E52; E58; 330; Independence; accountability; monetary policy; fiscal policy; expert committees; institution design